Correlation And Dispersion Of Marine Debris To Mollusca In The Interidal Zone - Eugenius Alfred Renjaan; Dortje Theodora Silubun; Dullah Irwan Latar; Marvin Mario Makailipessy; Megawati Elisabet Juley (Green Publisher Indonesia, 2021)
The research was carried out on Langgur Beach from January to March 2021. The purpose of this study was to determine the correlation and dispersion of marine debris to molluscs in the Intertidal Zone of Langgur Beach, the edge of the Rosenberg Strait, Kei Islands, Indonesia. The data collection method of this research is the quadratic method. The results of the study noted that the total marine debris accumulated at 21 sampling points amounted to 7,596 items consisting of 14 categories of marine debris and 6 species of Mollusca were found. The results of the analysis show that the dispersion of surface marine debris and marine debris in the sediments are scattered in groups, the dispersion per type of macrozoobenthos on the surface and in the sediments is scattered in groups, regularly and randomly. The results of the analysis also showed a positive correlation between marine plastic debris on the sediment surface and the bivalves of Gafrarium pectinatum on the sediment surface.